Artificial intelligence in traditional medicine: evidence, barriers, and a research roadmap for personalized care - Jongjiamdee, Ketmanee; Pornwonglert, Pimnipa; Na Bangchang, Nutnichar; Akarasereenont, Pravit (Frontiers in Artificial Intelligence, 2025)
BackgroundTraditional medicine (TM) systems such as Ayurveda, Traditional Chinese Medicine (TCM), and Thai Traditional Medicine (TTM) are increasingly intersecting with artificial intelligence (AI).ObjectiveTo synthesize how AI is currently applied to TM and to outline barriers and research needs for safe, equitable, and scalable adoption.MethodsWe conducted a targeted narrative mini review of peer reviewed studies (2017–Aug 2025) retrieved from PubMed, Scopus, and Google Scholar using terms spanning TM (Ayurveda/TCM/TTM) and AI (machine learning (ML), natural language processing (NLP), computer vision, telemedicine. Inclusion favored studies with reported methods and, when available, performance metrics; commentary and preprints without data were excluded.FindingsCurrent evidence supports AI assisted diagnostic pattern recognition, personalization frameworks integrating multi source data, digital preservation of TM knowledge, telemedicine enablement, and AI supported herbal pharmacology and safety assessment. Reported performance varies and is context dependent, with limited prospective external validation.LimitationsEvidence heterogeneity, small datasets, inconsistent ontologies across TM systems, and nascent regulatory pathways constrain real world deployment.ConclusionAI can augment TM education, research, and clinical services, but progress requires standards, culturally informed datasets, prospective trials, and clear governance. We propose a research roadmap to guide rigorous and ethical integration.